G114(P) The effects of sleeping position on the ventilatory response to hypoxia and hypercarbia. (27th April 2015) - Rossor, T; Ali, K; Trenear, R; Hannam, S; Rafferty, GF; Greenough, A
Abstract : Aims: The association of a higher rate of sudden infant death syndrome with prone compared to supine sleeping is well documented; the odds ratio for prone versus supine sleeping being 13.9. The mechanisms, however, remain uncertain. Our aims, therefore, were to determine if prone compared to supine sleeping was associated with impaired responses to hypoxia and hypercarbia. Methods: Infants born at 36 weeks post menstrual age or greater without respiratory problems were recruited from the postnatal ward. Physiological measurements were carried out when the infants were in quiet sleep. The hypoxic challenge was delivered via a nasal mask using 15% oxygen. Respiratory flow was measured using a pneumotachograph connected to the mask. Data were acquired and displayed in real time. Tidal volume was determined by digital integration of the flow signal. Minute volume (MV) was calculated on a 10 s average. In both positions, baseline ventilation was measured for five minutes whilst the infant was breathing medical air and then the infant's ventilatory response to inhalation of 15% oxygen was assessed for five minutes. The challenge was stopped if the oxygen saturation dropped to 85%. Infants respond to hypoxia with a biphasic response, first an increase then a decline in ventilation. The maximum MV, the hypoxic decline in MV and the time to the hypoxic decline were calculated. In each position, following a washout period, 4% carbon dioxide (CO2 ) in air was delivered for five minutes. The magnitude of increase in MV and the time constant of the increase in MV were calculated. Results: Fifty infants were studied. During exposure to 15% oxygen, the time to the start of the hypoxic decline was shorter in the prone compared to the supine position (81 s (6–295) versus 155 s (2–307)), p = 0.02. The time constant of the response to 4% CO2 was longer in the prone compared to the supine position (68 s (5–250) versus 36 s (3–220)), p = 0.022. Conclusion: Our results demonstrate a damped response to ventilatory challenges in the prone compared to the supine position.